Rapid increase in coral cover on an isolated coral reef, the Ashmore Reef National Nature Reserve, north-western Australia - Ceccarelli, D.; Richards, Zoe; Pratchett, M.; Cvitanovic, C. (CSIRO Publishing, 2011)
Against a background of coral reef ecosystem decline, understanding the propensity for coral communities to recover after acute disturbances is fundamental to forecasting and maintaining resilience. It may be expected that offshore reef ecosystems are less affected by anthropogenic disturbances compared with reefs closer to population centres, but that recovery may be slower on isolated reefs following disturbances. To test the hypothesis that community recovery is slow in isolated locations, we measured changes in coral cover and relative abundance of coral genera over a 4 year period (200509) at Ashmore Reef, north Western Australia, following severe bleaching. The percent cover of hard coral tripled, from 10.2% (±1.46 s.e.) in 2005 to 29.4% (±1.83 s.e.) in 2009 in all habitats (exposed and lagoonal) and depth zones (25 and 810m), and the percent cover of soft corals doubled, from 4.5% (+0.63 s.e.) in 2005 to 8.3% (+1.4 s.e.) in 2009. Significant shifts in the taxonomic composition of hard corals were detected. Our results imply that coral recovery in isolated locations can occur rapidly after an initial delay in recruitment, presumably through the interacting effects of self-recruitment and reduced exposure to additive impacts such as coastal pollution. © 2011 CSIRO.